Rhizobacteria activates (+)‐δ‐cadinene synthase genes and induces systemic resistance in cotton against beet armyworm (Spodoptera exigua). (5th February 2016) - Zebelo, Simon; Song, Yuanyuan; Kloepper, Joseph W.; Fadamiro, Henry
Abstract: Gossypol is an important allelochemical produced by the subepidermal glands of some cotton varieties and important for their ability to respond to changing biotic stress by exhibiting antibiosis against some cotton pests. Plant growth‐promoting rhizobacteria (PGPR) are root‐colonizing bacteria that increase plant growth and often elicit defence against plant pathogens and insect pests. Little is known about the effect of PGPR on cotton plant–insect interactions and the potential biochemical and molecular mechanisms by which PGPR enhance cotton plant defence. Here, we report that PGPR ( Bacillus spp.) treated cotton plants showed significantly higher levels of gossypol compared with untreated plants. Similarly, the transcript levels of the genes (i.e. (+)‐ δ ‐cadinene synthase gene family) involved in the biosynthesis of gossypol were higher in PGPR‐treated plants than in untreated plants. Furthermore, the levels of jasmonic acid, an octadecanoid‐derived defence‐related phytohormone and the transcript level of jasmonic acid responsive genes were higher in PGPR‐treated plants than in untreated plants. Most intriguingly, Spodoptera exigua showed reduced larval feeding and development on PGPR‐treated plants. These findings demonstrate that treatment of plants with rhizobacteria may induce significant biochemical and molecular changes with potential ramifications for plant–insect interactions. Abstract : Our results suggest that PGPR treatment can enhance plant defense against insect herbivory by triggering induced systemic resistance. Our data showed that PGPR treatment elicit the expression of JA related genes and induce increased levels of JA that might lead to induction of transcripts of gossypol related genes and increased levels of gossypol which resulted in reduced herbivory by S . exigua larvae.